UPAYA GURU DALAM MENGATASI KESULITAN BELAJAR SISWA - Lia Fatmasari; Ariga Bahrodin (Fakultas Psikologi Universitas Wijaya Putra, 2022)
Learning difficulties can be interpreted as a problem or condition where students experience obstacles in the learning process. Barriers experienced by students occur can be realized or not realized whether it is psychological, sociological, or the learning process. There is also a focus in this research, namely; Learning Difficulties Experienced by Class III Students at MI Miftahul Huda Tanjunganom Diwek Jombang, Aspects Affecting Students' Learning Difficulties, Teacher's Efforts in Overcoming Learning Difficulties for Class III Students. The purpose of this research is to find out what learning difficulties are experienced by Class III students at MI Miftahul Huda Tanjunganom Diwek Jombang, the factors that influence student learning difficulties, and the teacher's efforts in overcoming student learning difficulties. This research uses a qualitative research approach. Methods of data collection using observation, interviews, and documentation. The data analysis method uses data reduction, data presentation, conclusion drawing and verification. The method of checking the validity of the data uses data triangulation. The results of research on Teacher's Efforts in Overcoming Learning Difficulties for Class III Students are; Learning difficulties experienced by students are difficulties in mastering the material, mastering concepts, and mastering foreign languages. Aspects Affecting Student Learning, namely at least learning attention, low learning motivation, and very fast teacher delivery procedures. The teacher's efforts are providing tutorials to students, holding remedial teaching.